Design and Development of Integrated Arterial Signal Control Model - Vasudevan, Meenakshy; Chang, Gang-Len (Transportation research record, 2006)
This paper presents an arterial signal control system that provides arterial progression while optimizing signal timing plans at each intersection along the arterial. The proposed system is divided into two levels: progression control level and intersection control level. At the progression control level, arterial progression is provided by maximizing bandwidths using a modified version of the multiband model. In this study, unlike most bandwidth maximization models, queue clearance time and minimum green time are not prespecified, but are computed as a function of the existing queue at an intersection. At the intersection control level, signal timings are optimized for each intersection by minimizing a weighted combination of vehicle queue lengths, intersection control delays, and vehicle stop times, subject to bandwidths generated at the progression control level. The effectiveness of the system was evaluated through a case study conducted with CORSIM. Results showed that the proposed model was superior to actuated signal control implemented in the field and to the alternative that used the multiband model for signal progression. The proposed model resulted in significant reductions to control delays, stop times, and queues in addition to increases in throughput and speeds. Compared with the multiband model, the proposed model reduced arterial queues by 11%, control delays by 12%, and stop times by 14%. Compared with actuated signal control, benefits were greater, with reductions of 24% in vehicle queues, 17% in control delays, and 15% in stop times along the arterial.